Sukuk structure with embedded options as a risk mitigation tool / Roslina Mohamad Shafi, Nur Afizah Muhamad Ariffin and Norhana Salamudin - Mohamad Shafi, Roslina; Muhamad Ariffin, Nur Afizah; Salamudin, Norhana (Research Management Institute (RMI), 2013)
Sukuk market has grown tremendously and has gained attention from many countries.Various innovation has been designed to ensure the marketability of such instruments. However, these innovations have generated various shariah and financial issues and controversies. Among others, is the issue of the sukuk risk whereby the risk structure needs to be disclosed and conformed with shariah values. Even though sukuk is recognized as one of the Islamic financial products, it does not necessarily mean that it is free from the elements of risk. Even Islam has acknowledged the concept of risk as al ghurm bi al ghunm (entitlement to return is related to the liability of risk) in the application of muamalah (transaction, trade). Consequently, the aim of this paper is to suggest the application of sukuk with embedded options as to mitigate the risk faced by sukuk holders. Previous research has suggested the use of embedded options as a way to mitigate the risk. This paper will cover and discuss the issues pertaining to sukuk structures, the shariah values and the risk mitigation technique. A proposed sukuk structure and the mathematical model for finding the value of the real asset will also be covered in this paper. This study concludes with limitations of the study and recommendation for future research.